Effects of soils flooding. II. Influence on nutrient uptake and growth of rice (Oriza sativa) - Moraes, José Francisco Valente (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to study the influence of waterlogging on nutrient uptake and growth of rice. The experiment was composed of 16 treatments (4 soils and 4 levels of phosphorus, corresponding to 0, 40, 80 and 120 kg/ha), with 3 replications. Immediately after sowing, the soils were flooded. Four rice plants (Oriza sativa L. var. Sinaloa A 68) were grown in each pot. After 84 days the above ground portions of the plants were harvested. The dry matter weight was used as the yield index. Growth was extremely limited in all treatments. The quantitative chemical analysis of P, N, K, Ca, Mg, Fe and Mn in the stems and leaves indicated that the poor growth was caused by multiple nutritional deficiencies. Among these, deficiencies of phosphorus, potassium, calcium and magnesium were involved. The detected deficiencies were not caused by lack of nutrients in the soils but by alterations in the absorption process. These alterations were caused by soil reduction, and the accompanying presence of organic acids and other products of anaerobic decomposition in the root zone.